Development Assessment Of Acid Base Based On Science Process Skill - theresia samosir; chansyanah diawati; nina kadaritna (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
Research And Development has the objective to develop science process skills based assessment (KPS). The method used in the research and development is a Research And Development (R D). Characteristic assessment generated by finite trials are as follows : 1) Test the opinion of interesting 76,45% of student at the high category, 2) Test the suitability of the content of the material ini the opinion of the teacher 82,78% is very high category, and 3)Test readability 83,8% according to the teacher’s category is very high category and amounted to 76,4% according to the student’s category is high category. In the process of the development of this assessment, there are obstacles that faced some problems are difficult to describe both macroscopic, submicroscopic, and symbolic that the translation of assessment is a simple matter becomes difficult.Keywords : Assessment, KPS, Acid Bases